Comparative clinical prognosis of massive and non‐massive pulmonary embolism: A registry‐based cohort study. (19th December 2020) - Blondon, Marc; Jimenez, David; Robert‐Ebadi, Helia; Del Toro, Jorge; Lopez‐Jimenez, Luciano; Falga, Conxita; Skride, Andris; Font, Llorenç; Vazquez, Fernando Javier; Bounameaux, Henri; Monreal, Manuel; ,
Abstract: Aims: Little is known about the prognosis of patients with massive pulmonary embolism (PE) and its risk of recurrent venous thromboembolism (VTE) compared with non‐massive PE, which may inform clinical decisions. Our aim was to compare the risk of recurrent VTE, bleeding, and mortality after massive and non‐massive PE during anticoagulation and after its discontinuation. Methods and results: We included all participants in the RIETE registry who suffered a symptomatic, objectively confirmed segmental or more central PE. Massive PE was defined by a systolic hypotension at clinical presentation (<90 mm Hg). We compared the risks of recurrent VTE, major bleeding, and mortality using time‐to‐event multivariable competing risk modeling. There were 3.5% of massive PE among 38 996 patients with PE. During the anticoagulation period, massive PE was associated with a greater risk of major bleeding (subhazard ratio [sHR] 1.72, 95% confidence interval [CI] 1.28–2.32), but not of recurrent VTE (sHR 1.15, 95% CI 0.75–1.74) than non‐massive PE. An increased risk of mortality was only observed in the first month after PE. After discontinuation of anticoagulation, among 11 579 patients, massive PE and non‐massive PE had similar risks of mortality, bleeding, and recurrent VTE (sHR 0.85, 95% CI 0.51–1.40), but with different case fatality of recurrent PE (11.1% versus 2.4%, P = .03) and possibly different risk of recurrent fatal PE (sHR 3.65, 95% CI 0.82–16.24). Conclusion: In this large prospective registry, the baseline hemodynamic status of the incident PE did not influence the risk of recurrent VTE, during and after the anticoagulation periods, but was possibly associated with recurrent PE of greater severity.